A phase 2 study of carfilzomib, cyclophosphamide and dexamethasone as frontline treatment for transplant-eligible MM with high-risk features (SGH-MM1) - Chen, Yunxin (SPRINGERNATURE, 2021)
10.1038/s41408-021-00544-x